Relationship between types of Benefit (leave, loan and retirement plan) and Employees’ Retention - Rusli, Ahmad; Eileen Pei Yei, Toh; Sopian, Sopian (IJERN, 2013)
The purpose of this research was to determine relationship between the types of benefit (leave, loan and retirement plan) and employees’ retention. A total of 70 respondents are selected from one public university in East Malaysia and become the respondent for this study. Questionnaire method was used for data collection. Parametric test was conducted for checking the goodness of the data. The hypotheses test showed that there was a positive relationship between leave, loan and retirement plan with employees’ retention. In addition, leave was the dominant types of benefit in retaining the employees among the public university employees. The implication of this research indicates that the combination of non-monetary and monetary types of benefit do affect the employees’ retention. In future study, researcher should expand the types of benefit such as allowances, insurances which aimed to retain the employees.